Part-time and Limited-term Faculty in Alberta's Colleges - Barnetson, Bob (Canadian Journal of Higher Education, 2001)
This paper argues that the number of part-time and limited-term faculty in Alberta's (Canada) public colleges and technical institutes and their substantially different employment conditions indicate the existence of a dual labour market at five institutions. Further analysis demonstrates that women disproportionately receive part-time and limited-term appointments.